2015
DOI: 10.18865/ed.25.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Peroxisome Proliferator-activated Receptors (PPARs) α, γ and δ Gene Polymorphisms for Obesity and Metabolic Syndrome Association in the Multi-ethnic Malaysian Population

Abstract: Objective: This study aimed to investigate the association of peroxisome proliferatoractivated receptor (PPAR) genes PPARα L162V, PPARγ2 C161T and PPARδ T294C single nucleotide polymorphisms (SNPs) with obesity and metabolic syndrome (Met-S) in a multi-ethnic population in Kampar, Malaysia.Methods: Socio-demographic data, anthropometric and biochemical measurements (plasma lipid profile, adiponectin and interleukin-6 [IL-6] levels) were taken from 307 participants (124 males; 180 obese; 249 Met-S; 97 Malays, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
6
1
1
Order By: Relevance
“…Besides, our frequencies differ from those found in Spanish Mediterranean, Brazilian and Croatian populations (Francès et al 2008;Chen et al 2010;Nadalin et al 2014). "VV" genotype was not found in Croatian population (Nadalin et al 2014) and in multi-ethnic Malaysian population (Chia et al 2015). Similarly we found no subjects with "VV" genotype in our control group whereas we found only five subjects in our patient group.…”
Section: Discussioncontrasting
confidence: 96%
“…Besides, our frequencies differ from those found in Spanish Mediterranean, Brazilian and Croatian populations (Francès et al 2008;Chen et al 2010;Nadalin et al 2014). "VV" genotype was not found in Croatian population (Nadalin et al 2014) and in multi-ethnic Malaysian population (Chia et al 2015). Similarly we found no subjects with "VV" genotype in our control group whereas we found only five subjects in our patient group.…”
Section: Discussioncontrasting
confidence: 96%
“…In the aspect of pathophysiology of MetS, hyperglycemia is considered as a key factor. Hyperinsulinemia, insulin resistance, and hyperglycemia are increasing proliferation, angiogenesis, damage to the DNA molecule by oxygen active forms due to glucose excess, cellular mobility, and apoptosis 17–19 . From the results of previous literatures, it has been suggested that, MetS affects tumor cells cancer and finally increasing the risk of cancer through the change in insulin receptor expression as well as the activation/inactivation of the growth and transcription factors, their receptors 17,2022 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that one MS component hyperglycaemia was independently associated with increased HNC risk. Hyperglycaemia is considered to be a critical factor in the pathophysiology of MS. Hyperglyceamia, Hyperinsulinemia and insulin resistance are increasing proliferation, angiogenesis, and the destruction of DNA molecules by oxygen-active forms caused by excess glucose, cell migration and apoptosis [29][30][31] . Previous studies suggested that MS elevated the incidence risk of cancer through the change of insulin receptors and activation of growth and transcription factors 32,33 .…”
Section: Resultsmentioning
confidence: 99%